Men's and Women's Health Beliefs Differentially Predict Coronary Heart Disease Incidence in a Population-Based Sample. (April 2013) - Rom Korin, Maya; Chaplin, William F.; Shaffer, Jonathan A.; Butler, Mark J.; Ojie, Mary-Jane; Davidson, Karina W.
Objective . To examine gender differences in the association between beliefs in heart disease preventability and 10-year incidence of coronary heart disease (CHD) in a population-based sample. Methods . A total of 2, 688 Noninstitutionalized Nova Scotians without prior CHD enrolled in the Nova Scotia Health Study (NSHS95) and were followed for 10 years. Risk factors, health behaviors, and incident CHD were assessed. Participants responded "yes" or "no" to a question about heart disease preventability. Survival models, adjusted for age, income, total and high-density lipoprotein cholesterol, and systolic blood pressure, were used to estimate the relation between health belief and incident CHD. Gender differences in the relation between health beliefs and health behaviors were assessed. Results . Gender was a significant moderator of the relation between belief and CHD incidence; specifically, women who believed heart disease could be prevented were less likely to have incident CHD events compared with women who believed heart disease could not be prevented (hazard ratio [HR] = 0.36, 95% confidence interval [CI] = 0.24-0.55, p < .001). This relation was not found for men. Belief was also related to smoking behavior for women (β = −0.70, odds ratio [OR] = 0.50, 95% CI = 0.33-0.74, p = .001) but not for men. Smoking significantly mediated the relation between health beliefs and incident CHD for women ( z = −1.96, p = .05), but not for men. Conclusion . Health belief in prevention and subsequent smoking was an important independent predictor of incident CHD in women but not in men.